HUKUMAN MATI DALAM ISLAM ANTARA TEKS SUCI DAN HAK ASASI MANUSIA - Mardhatillah Mardhatillah (Yayasan An-Nur Meunara Baro, 2025)
The death penalty in Islam is a complex and ongoing issue, especially in light of contemporary human rights discourse. This article critically examines the theological foundations of capital punishment in Islamic sacred texts, such as the Qur’an and Hadith, focusing on its application in the contexts of qishash, hudud, and taʿzir. On the other hand, it explores the tension between the implementation of Islamic criminal law and global human rights principles, particularly the right to life as protected by the Universal Declaration of Human Rights and the ICCPR. The research employs a normative-legal and contextual hermeneutical approach, combined with a comparative analysis of the implementation of the death penalty in Muslim-majority countries such as Saudi Arabia, Iran, and Indonesia. The findings indicate that although Islam provides theological legitimacy for the death penalty, its application is conditional, procedural, and open to reinterpretation based on humanitarian objectives through the framework of maqāṣid al-sharīʿah. Furthermore, there is a growing trend among contemporary Muslim scholars to reassess the death penalty within a framework of substantive justice and current socio-political contexts. The article recommends a reform of Islamic criminal law grounded in restorative justice, victim rights, and protection against judicial errors. Thus, Islamic law can uphold its normative integrity while remaining responsive to evolving universal values.